FREQUENCY OF HYPERURICEMIA IN SUBJECTS WITH UNSTABLE ANGINA/MYOCARDIAL INFARCTION AND THEIR PROGNOSIS - Amir Rashid Qureshi; Ali, Syed Affan; Mir Jalal; Syed Imran Ahmed Kazmi; Atifa Gillani; Wahaj (Journal of Ayub Medical College Abbottabad, 2022)
ABSTRACT Background: Inhibition of nitric oxide synthesis and stimulation of smooth muscle proliferation by increased serum levels of uric acid play an important role in accelerated atherogenesis in the vessels of patients with hyperuricemia. The objective of the study was to determine the frequency of hyperuricemia in patients with acute coronary syndrome and their in-hospital outcomes. Methods: This cross-sectional study was conducted in the cardiology department of Ayub Teaching Hospital, Abbottabad from 1st September, 2018 to 28th February, 2019. A total of 199 patients diagnosed with acute coronary syndrome (ACS) were enrolled in this study using non-probability consecutive sampling. Diagnosis of ACS was made on history, electrocardiogram (ECG) findings and on the presence of elevated cardiac biomarkers. Serum uric acid was checked within 24 hours of presentation and patients were grouped into hyperuricemic and normouricemic groups according to uric acid levels. Next in-hospital outcomes were compared between the two groups by comparing the presence or absence of complications. The data was collected on a structured proforma and was analyzed statistically by using SPSS version 16. Results: Out of 199 patients, 146 (73.37%) were male and 53 (26.63%) were female. The mean age of the study participants was 57.99 ± 6.07 years with a range of 48-68 years. Hyperuricemia was diagnosed in 50 (25.13%) study participants. Among complications, 15 patients (7.94%) had cardiogenic shock, 27 (13.57%) had heart failure, 10 (5.03%) had cardiac arrhythmias, 16 (8.04%) had conduction defects and hyperuricemia was diagnosed in 50 (25.13%) patients. Cardiogenic shock was more common in patients with hyperuricemia (p < 0.05). Conclusion: Hyperuricemia is associated with a number of significant adverse outcomes for patients with an acute coronary event. Regular screening / monitoring of serum uric acid level in general population can prevent the direct and indirect morbidity associated with hyperuricemia. Keywords: Acute coronary Syndrome, Hyperuricemia, Uric Acid, cardiogenic shock, mortality, ST elevation myocardial infarction (STEMI), non ST elevation acute coronary syndrome (NSTE-ACS)